Perjuangan Perempuan Menghadapi Kekuasaan Dalam Lakon â€œSusi Duyungâ€: Ludruk Budhi Wijaya - M. Shoim Anwar; Listyo Ambarwati (Universitas PGRI Adi Buana Surabaya, 2017)
Ludruk Budi Wijaya Group is a cultural actor who is active in maintaining and developing the arts of thepeople. The characteristic of ludruk as a critical stage art is maintained, including the structure of the show. Ludruk isa channel for the aspirations of the little people and represents their lives. The